2003
DOI: 10.4049/jimmunol.171.9.4485
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-12 Receptor β1 in Regulation of T Cell Response by APC in Experimental Autoimmune Encephalomyelitis

Abstract: IL-12 was thought to be involved in the development of experimental autoimmune encephalomyelitis (EAE), a Th1 cell-mediated autoimmune disorder of the CNS. However, we have recently found that IL-12 responsiveness, via IL-12Rβ2, is not required in the induction of EAE. To determine the role of IL-12Rβ1, a key subunit for the responsiveness to both IL-12 and IL-23, in the development of autoimmune diseases, we studied EAE in mice deficient in this subunit of IL-12R. IL-12Rβ1−/− mice are completely resistant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 62 publications
8
59
0
2
Order By: Relevance
“…However, they provided no explanation for why abolishing IL-12(R)-mediated signaling in p35-or IL-12Rb2-deficient mice yielded a phenotype of enhanced disease susceptibility/severity [9][10][11][12]14]. Our finding of the exclusive capacity of IL-12 to suppress the release of IL-17 from activated human T cells provides a possible molecular mechanism behind this apparent anti-inflammatory activity of IL-12.…”
Section: Il-12 Inhibits Il-23-and Il-18-mediated Il-17 Production By mentioning
confidence: 68%
See 1 more Smart Citation
“…However, they provided no explanation for why abolishing IL-12(R)-mediated signaling in p35-or IL-12Rb2-deficient mice yielded a phenotype of enhanced disease susceptibility/severity [9][10][11][12]14]. Our finding of the exclusive capacity of IL-12 to suppress the release of IL-17 from activated human T cells provides a possible molecular mechanism behind this apparent anti-inflammatory activity of IL-12.…”
Section: Il-12 Inhibits Il-23-and Il-18-mediated Il-17 Production By mentioning
confidence: 68%
“…Accordingly, Zhang et al [13] reported that IL-12Rb1-deficient mice are resistant to EAE. Unexpectedly, however, IL-12p35-and IL-12Rb2-deficient mice, in which only the IL-12 and not the IL-23 function is affected, are more susceptible and developed more severe pathology than wild-type mice [9,10,12,13], with increased levels of IL-23p19 in spleen cells compared to wild-type littermates [13,14]. It was concluded from these studies that IL-12 is not critical for disease development, and may even play an undefined protective role.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, APCs that produce large quantities of IL-12 and IFN-γ induce Th1 responses; APCs that produce low amounts of IL-12 but a high level of MCP-1 preferentially induce Th2 responses, whereas APCs that produce a low level of IL-12 but a high level of IL-10 induce regulatory T cell (Tr) responses (de Jong et al, 2005). In addition, our laboratory found that APCs of IL-12Rβ1 −/− mice, which lack both IL-12 and IL-23 signaling, exhibit bias toward inducing Th2 response (Zhang et al, 2003). Dendritic cells (DCs) and macrophages are the two most important types of professional APCs, with similar functions and profiles of secreted cytokines (Lee et al, 2007;Saalmüller, 2006;Unanue, 1984).…”
Section: Introductionmentioning
confidence: 87%
“…Viability of the final APC population used for all experiments was >97% (data not shown). These MOG and/or M-CSFtreated APCs were washed and mixed with purified CD4 + or CD8 + T cells at a ratio of 1:1 as previously described (Zhang et al, 2003), and cultured at a final density of 2.0 × 10 6 /ml in RPMI 1640 supplemented with 10% FCS and 10 μg/ml of MOG . To determine APCdriven Tr differentiation, immunostaining for cell surface molecules and intracellular Foxp3 expression was carried out after 5 days of culture.…”
Section: Co-culture System For Tr Differentiation and Lymphocyte Prolmentioning
confidence: 99%
“…7,8 In contrast, several reports suggested a controversial role for IL-12 in the pathogenesis of EAE; p35-and IL-12Rb2-deficient mice still remained susceptible to EAE, whereas p40-and IL-12Rb1-deficient mice did not develop EAE. [9][10][11] A recent report showed that p19-deficient mice did not develop EAE, demonstrating that IL-23 rather than IL-12 was involved in the pathogenesis of EAE. 12 p40, the common subunit of IL-23 and IL-12, is experimentally secreted when neither p19 nor p35 is expressed, and can bind to IL-12Rb1, acting as an antagonist for IL-12; [13][14][15][16] thus, the production of p40 in vivo can be a novel self-regulatory process to suppress IL-12 functions.…”
Section: Introductionmentioning
confidence: 99%